Effects of mannose-oligosaccharide on bacterial community of gut in broilers - WEN Ruo-zhu; JIANG Yun; LIU Ze-xing; CHENG Ling-hao; DENG Yu; GAO Feng; ZHOU Guang-hong (浙江大学学报. 农业与生命科学版)
DNA was extracted from the broiler's faecal samples and the V6-V8 regions of bacterial 16S rDNA were amplified and analyzed by denaturing gradient gel electrophoresis (DGGE) to monitor the development of bacterial community in faeces of broilers and the effects of mannose-oligosaccharide supplementation on bacterial community of intestinal tract. The broiler chickens were randomly assigned to 2 dietary treatments: Group I (control) was fed corn-soybean meal based diet, and group II was fed basal diet supplemented with 0.2% MOS at 1-21 d and 0.1% MOS at 22-42 d, each of which were assigned to 4 replicates of 24 birds each. Results showed that the major species in gut were Lactobacilli, and each region of the gut developed its own unique microbial profile, and this community became more complex as the chickens grew older. The diversity of the bacterial community in cecum was richer than any others. The similarity of the bacterial community at each age was as low as approaching to the distal gut. The group with MOS enhanced the growth of Lactobacilli in the gut, while inhibited the growth of Clostridium to maintain gut health. It was also found that the highest similarity of the bacterial community of gizzard, duodenum, jejunum, ileum and cecum in control was (group Ⅰ) 77%, 68%, 72%, 49%, 63% respectively, while group II was 76%, 84%, 72%, 49%, 63% respectively. The results demonstrated that age of chickens had the most profound effect on these characteristics of the microbiota.